Patriarch Tikhon and autocephaly of the Polish Orthodox Church of 1924 - Anastasiya Chibisova (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
In the early 1920s, the Polish government conducted active negotiations in Moscow with Patriarch Tikhon (Bellavin) on the issue of his blessing the autocephaly of the Polish Orthodox Church. Up to now, in Russian historiography has been only one document that reveals the attitude of Patriarch Tikhon to the idea of the independent existence of the Polish Church. It is a text of a resolution made by the Patriarch at the request of the Polish bishops to grant independence to the Polish Church. It was published in a collection of documents from M. E. Gubonin’s archive. This article is intended to expand our knowledge of Patriarch Tikhon’s position taken during negotiations with Polish diplomats in the fi rst half of the 1920s, as well as to introduce new documents related to the topic. The article describes in detail the course of negotiations and their outcome. Special attention is paid to the moderateness of the position of the Patriarch as to the Polish question and to the fact that he consistently off ered broad autonomy to the Polish Church. Another conclusion is that Patriarch Tikhon’s position facilitated the negotiations of the Polish government about the autocephaly with Constantinople Patriarchate. These negotiations resulted in its acknowledgement of independence of the Polish Church in 1924. The article is accompanied by an appendix.